Cultural Activity of Prisoners in Poland and Hungary in the Aspect of Law and Practices - Miklósi, Márta; Molnár, Attila Károly; Becker-Pestka, Daria (INSTED: Interdisciplinary Studies in Education & Society, 2023)
In our study, we began with the premise that education strives to successfully reintegrate prisoners into society. Under the term education, we consider several actions aimed at reintegration, including elementary, secondary and vocational training. What's more, we think any cultural activity can possibly support the right way of life after release. All of these must be based on the cultural self-expression of prisoners. In the study, we attempt to present the possible moments of the cultural life of the prison and the exploitation of prisoners' rights to culture. Within this, we draw attention to community cultural opportunities and their impact on inmates. We declare that cultural activities in prisons are highly important for reintegration as cultural programmes and artistic actions bring prisoners closer to the nature of the free world. We will discuss two countries [regarding the topic] - Poland and Hungary - and show the diversity of the cultural activities available to prisoners. We will also highlight a few examples of these.